A comparative study between self-perception of walking ability, balance and risk of fall with actual clinical assessment - Nurulaini A; Syahnaz MH; Shamsul AS; Teh Rohaila Jamil (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Gait and balance disorder are among the most common causes of falls in elderly and often lead to injury, disability and loss of independence. However, there might be a discrepancy between elderly’s perception of their own walking ability, balance, risk of fall with doctor’s evaluation. The aim of this study was to compare perception of the elderly’s walking ability, balance and risk of fall with clinical assessment. This cross sectional study was done in a Primary Care Clinic which involved elderly > 60 years using systematic random sampling. Participants completed a self-administered questionnaire comprising of sociodemographic data and question assessing their perception of ability of walking, balance and risk of fall. Actual clinical assessment was done using Tinetti Performance Oriented Mobility Assessment. Most of the participants perceived they had good walking (84.4%) and balance ability (77%). A small proportion (11.5%) agreed that they are at risk of fall. There was a good agreement in walking ability (k: 0.702, p: <0.001), moderate agreement in balance (k: 0.546, p: <0.001) but poor agreement in the risk of fall (k: 0.300, p: <0.001). Multiple logistic regression demonstrated that factors associated with participant’s perception of risk of fall are age, having stroke and taking psychotropic drugs. A discrepancy is observed between self-perception of balance and risk of fall with actual assessment. Advancing age, history of stroke and psychotropic drugs were significantly associated with increased perception of fall risk. The future intervention programme need to focus on creating awareness particularly among those who have these factors.